Optimizing maternal fat suppression with constrained image‐based shimming in fetal MR. Issue 1 (29th July 2018) - Gaspar, Andreia S.; Nunes, Rita G.; Ferrazzi, Giulio; Hughes, Emer J.; Hutter, Jana; Malik, Shaihan J.; McCabe, Laura; Baruteau, Kelly P.; Rutherford, Mary A.; Hajnal, Joseph V.; Price, Anthony N.
Abstract : Purpose: Echo planar imaging (EPI) is the primary sequence for functional and diffusion MRI. In fetal applications, the large field of view needed to encode the maternal abdomen leads to prolonged EPI readouts, which may be further extended due to safety considerations that limit gradient performance. The resulting images become very sensitive to water‐fat shift and susceptibility artefacts. The purpose of this study was to reduce artefacts and increase stability of EPI in fetal brain imaging, balancing local field homogeneity across the fetal brain with longer range variations to ensure compatibility with fat suppression of the maternal abdomen. Methods: Spectral Pre‐saturation with Inversion‐Recovery (SPIR) fat suppression was optimized by investigating SPIR pulse frequency offsets. Subsequently, fetal brain EPI data were acquired using image‐based (IB) shimming on 6 pregnant women by (1) minimizing B0 field variations within the fetal brain (localized IB shimming) and (2) with added constraint to limit B0 variation in maternal fat (fat constrained IB shimming). Results: The optimal offset for the SPIR pulse at 3 Tesla was 550 Hz. Both shimming approaches had similar performances in terms of B0 homogeneity within the brain, but constrained IB shimming enabled higher fat suppression efficiency. Conclusion: Optimized SPIR in combination with constrained IB shimming can improve maternal fat suppression while minimizing EPI distortions in the fetal brain.